A systematic review of the association between fibromyalgia and functional gastrointestinal disorders. (December 2020) - Erdrich, Sharon; Hawrelak, Jason A.; Myers, Stephen P.; Harnett, Joanna E.
Background: Fibromyalgia and functional gastrointestinal disorders (FGID) including irritable bowel syndrome (IBS) are common conditions presenting in clinical settings and are more prevalent in women. While the relationship between IBS and fibromyalgia has been demonstrated, a review of the prevalence of the broader group of FGID in adults with fibromyalgia has not been undertaken. The aim of this review was to systematically review the published literature, identifying the comorbidity of FGID in people with fibromyalgia, and to discuss the clinical implications, limitations of current research and areas of interest for future research Methods: Medline, Embase, CINAHL and Web of Science were searched during June 2019. Results were screened for original research articles meeting established criteria for identification of FGID in adults diagnosed with fibromyalgia. Results: A total of 14 studies involving 1340 adults with fibromyalgia, 363 healthy controls and 441 adults with other pathologies were included in this review. Only 1 of the 14 studies included surveyed the full range of FGID . Functional gut disorders were matched to Rome II criteria for reporting and comparison. In addition to increased abdominal pain and functional bloating or gas, IBS of mixed-pattern and constipation-types appear to be more prevalent than diarrhoea-predominant IBS in adults with fibromyalgia. Conclusion: This review confirms previous reports that IBS is common in people living with fibromyalgia and suggests that IBS-mixed and constipation types predominate. An association with a range of FGID other than IBS is suggested, but data are limited. Research exploring the association between fibromyalgia and functional gastrointestinal dysfunction beyond IBS are warranted.